Hermeneutika Feminis: Kritik Atas Kesetaraan Fatima Mernissi - Lub Lyna Nabilata (Al-Adabiya: Jurnal Kebudayaan dan Keagamaan, 2018)
Cultural optics will always appear in every debate about feminism, as well as certain interpretive tendencies (read: pre-text) also involved (enveloped) and even come into play in them. Therefore, the emergence of different views even somewhat "biased" is considered normal. People in discussing feminism will not be able to position themselves really objectively without pretension, but can only maintain a distance from prejudices or “biases” that can unwittingly emerge. In Muslim feminist thought, they are still trapped in a crisis of interpretation and counter interpretation. This crisis arises because the methods or strategies used by opponents and supporters of gender equality in building and legitimizing each of their views are basically the same, namely by explaining certain parts of the text of the Qur’an or hadith that are appropriate and support their interests and views. The parts of the text are then considered as asl the most correct and original principles, which in turn tend to be interpreted unilaterally in accordance with their ideological interests and positions and at the same time eliminate unwanted meanings because they are contrary to their ideological interests. This eclectic reading model is caused by the inability to challenge the existing paradigm of reading the text, which does not consider the historical context, dialogical and communicative aspects of the text with its context, and its descriptive dimensions. In this article intending to criticize the interpretation of Fatima Mernissi, Mernissi seems to still have a subjective bias in assessing some of the problems of feminist interpretation regarding equality of men and women, and not occupying the core of the problem in the actual portion. As a result, this argument shows that Mernissi is still narrow in using her feminist approach, because the core feminist approach is actually sensitive to injustice and avoiding “bias” that can occur not only in gender issues, but can also occur in other areas related to sara (read: skin color, tribe, caste and others).